Editorial: Legumes and their microbiome in climate change mitigation - Monteoliva, Mariela Ines; Ruiz, Oscar A.; Fadong, Li (Frontiers Media, 2023)
Climate change accelerates or enhances the incidence of a variety of abiotic and biotic stresses on agricultural and forest productivity. By changing different aspects of agriculture management, we can lower the risk of climate change over plant-derived productivity, including food, fiber, and bioenergy. Legumes (Fabaceae) is the third largest family of flowering plants, with more than 20000 species. They play central roles in (human and animal) food and plant-based protein production. Legume crops emit fewer greenhouse gases (such as carbon dioxide and nitrous oxide, compared to other nitrogen-fertilized crops), allow more sequestration of carbon in soils, and save fossil energy inputs in the system by reducing N fertilizer needs.